2021
DOI: 10.3390/ijerph182312405
|View full text |Cite
|
Sign up to set email alerts
|

Did COVID-19 Pandemic Change People’s Physical Activity Distribution, Eating, and Alcohol Consumption Habits as well as Body Mass Index?

Abstract: This cross-sectional study aimed to evaluate whether COVID-19 had an impact on people’s (aged 18–74) physical activity distribution, eating, and alcohol consumption habits as well as body mass index. We interviewed 6369 people (4545 women and 1824 men) in Lithuania before the COVID-19 pandemic started and 2392 during COVID-19 (1856 women and 536 men). They were aged 18–74 years. We found that both genders had not stopped their physical activity (PA) completely because of lockdown imitations (for example, prohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 27 publications
1
19
0
2
Order By: Relevance
“…There is an increasing amount of evidence-based research showing that various forms and doses of physical activity (PA) or exercise are effective in combating many chronic diseases [ 1 , 2 ] and improving well-being and mental health [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. The health benefits of PA are influenced by age, sex, health, and body mass index (BMI) [ 10 , 11 , 12 , 13 ]. Studies have also shown that the effects of PA or exercise on the body are specific; that is, they are affected by the intensity, duration, type of muscle contraction, motor control, and other factors [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing amount of evidence-based research showing that various forms and doses of physical activity (PA) or exercise are effective in combating many chronic diseases [ 1 , 2 ] and improving well-being and mental health [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. The health benefits of PA are influenced by age, sex, health, and body mass index (BMI) [ 10 , 11 , 12 , 13 ]. Studies have also shown that the effects of PA or exercise on the body are specific; that is, they are affected by the intensity, duration, type of muscle contraction, motor control, and other factors [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, low PA promotes obesity, which in turn reduces motivation to perform PA [ 14 ] and encourages more frequent overeating because people cannot control their appetite [ 15 ]. Studies have shown that even during the COVID-19 pandemic, moderate PA (MPA), vigorous PA (VPA), or a combination of MPA and VPA (MVPA) did not change significantly, men and women reported eating less excessively than before, did not start consuming more alcohol, and their body mass index did not change [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence-based research indicates that various forms and amounts of physical activity (PA) are effective in combating many chronic diseases [1,2], improving well-being and mental health [3][4][5][6][7][8][9], and reducing all-cause mortality [10]. The effect of PA on various body functions is rather speci c; i.e., it depends on the nonlinear manner of muscle work intensity, duration, and load "doses" [11][12][13][14][15][16][17]2].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of PA on various body functions is rather speci c; i.e., it depends on the nonlinear manner of muscle work intensity, duration, and load "doses" [11][12][13][14][15][16][17]2]. In addition, the health bene ts of PA also depend on the individual's age, gender, health, and BMI [18, 10,5,19,2,6,7].…”
Section: Introductionmentioning
confidence: 99%